EXISTENCE OF TRAVELING WAVES BY MEANS OF FIXED POINT THEORY FOR AN EPIDEMIC MODEL WITH HATTAF-YOUSFI INCIDENCE RATE AND TEMPORARY IMMUNITY ACQUIRED BY VACCINATION. (2023) - MAMOUNI, HAMZA EL; HATTAF, KHALID; YOUSFI, NOURA
No abstract available